Yet Another ‘Feminist’ Perspective on Art History? (KULT_online, 2021)
The Art of Feminism: Images that Shaped the Fight for Equality provides a chronological, thematically well-structured overview of feminist history and the different roles artists and artworks played and play in it. The volume illustrates art history from a female perspective and addresses questions of race, class and sexuality in different historical contexts. It coherently and consistently provides a platform for marginalized artists, creating intersectional awareness of the inequalities characteristic (not only) of the art scene.